Sprezzatura concealing the effort of art from Aristotle to Duchamp - D'Angelo, Paolo (Columbia University Press, 2018)
The essence of art is to conceal art. A dancer or musician does not only need to perform with ability. There should also be a lack of visible effort that gives an impression of naturalness. To disguise technique and feign ease is to heighten beauty. To express this notion, Italian has a word with no exact equivalent in other languages, sprezzatura: a kind of unaffectedness or nonchalance.